2007
DOI: 10.1111/j.1553-2712.2007.tb02395.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Human Factor Design on the Use of Order Sets in the Treatment of Congestive Heart Failure

Abstract: Background: Although standardized physician order sets are often part of quality improvement projects, the specific design elements contributing to increased adoption and compliance with use often are not considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…Olson et al reported that pre-selecting a post-transfusion hematocrit order within a red cell transfusion order set increased frequency of testing from 8.3% to 57.4% after transfusion (10). Similar findings were observed for CPOE use in managing congestive heart failure (11), analgesic treatment for renal colic (12), and sepsis (13). According to the Medicare Clinical Laboratory Fee Schedule, our intervention resulted in savings of $5,955 during the study period ($10,455in the pre-period vs. $4,500 in the post intervention, at national median Medicare payment rate of $15.00 per urine culture)(14).…”
Section: Discussionsupporting
confidence: 65%
“…Olson et al reported that pre-selecting a post-transfusion hematocrit order within a red cell transfusion order set increased frequency of testing from 8.3% to 57.4% after transfusion (10). Similar findings were observed for CPOE use in managing congestive heart failure (11), analgesic treatment for renal colic (12), and sepsis (13). According to the Medicare Clinical Laboratory Fee Schedule, our intervention resulted in savings of $5,955 during the study period ($10,455in the pre-period vs. $4,500 in the post intervention, at national median Medicare payment rate of $15.00 per urine culture)(14).…”
Section: Discussionsupporting
confidence: 65%
“…Adoption of the BHCS heart failure order set is comparable to that reported for order sets implemented in the Grey Bruce Health Network in Canada ( 40% systemwide after 6 months) [22] and mirrored the 72% adoption of an emergency department heart failure clinical pathway 14 months postimplementation at a single suburban tertiary care hospital [23]. Similarly, previous studies have shown similar improvements in heart failure outcomes following implementation of hospital-based tools to increase standardization.…”
Section: Comparison To the Literaturesupporting
confidence: 65%
“…Multiple studies evaluating the use of standardized care bundles in the management of heart failure exacerbations were able to show reduced 30-day mortality and 30-day readmission rates. 26 28 Meanwhile, evidence-based care bundles have been used in the management of sepsis and septic shock with results significant for earlier administration of antibiotics, improved 30-day mortality, less utilization of vasopressors, and decreased length of stay. 29 31 Studies that examined care bundle use for surgical admissions have also proven to reduce length of stay and hospital costs.…”
Section: Introductionmentioning
confidence: 99%